Eclosión de quistes en dos especies de Dendrocephalus (Anostraca: Thamnocephalidae) de uso potencial como alimento en acuacultura - García, José Vicente (2000)
The use of Artemia salina nauplii as live food has significantly aided culture of commercial fish and shrimps in recent years. However, reported defficiencies in the nutritional value of some strains originated the study of freshwater fairy shrimps as an alternative to Artemia. This study presents cyst biometry for Dendrocephalus geayi and D. spartaenovae (Anostraca: Thamnocephalidae), and the effects of some physicochemical variables on cyst hatching. The biometric characteristics of D. geayi and D. spartanovae are within the size range of commercial Artemia strains. Favorable conditions to batch D. geayi are 30°C and conductivity near that of distilled water (<5 μmhos). For D. spartaenovae, these conditions are 28 °C and 280 μmhos. A very low salinity such as 1% inhibits hatching in both species.